Análisis de la sostenibilidad del modelo económico venezolano: chavismo, petróleo y distribución de la renta - Hernández-Martínez, D.; Pérez-Lagüela E. (Revista Iberoamericana de Estudios de Desarrollo)
This paper analyzes the Venezuelan economic model during the governments of Hugo Chávez and Nicolás Maduro (1999-2016), in order to find out if it is in a circumstantial crisis or in a bankruptcy of unsustainability. To do this, the fundamentals of the Chavista economic model are examined, analyzing the policies and reforms that have tried to reverse the structural problems of the Venezuelan economy. The emphasis on redistribution and social spending measures is the key in the popular legitimacy of successive governments. Then, it is described the importance of oil for the development of such policies, crucial element for the country’s growth and survival of the implanted model.